"Wrong place to get help": A field experiment on luxury stores and helping behavior. (2nd April 2016) - Lamy, Lubomir; Guéguen, Nicolas; Fischer-Lokou, Jacques; Guegan, Jérôme
Abstract: Three experiments were conducted in field settings. It was hypothesized that luxury stores may act as environmental reminders of materialism and that helpfulness would vary according to the presence or absence of such cues. Study 1 ( N  = 80) indicated that consumers coming out of famous brand stores displayed less helpfulness, as compared to mere passersby. Study 2 ( N  = 112) showed passersby were less helpful near a luxury brand store than in an ordinary street with no shops. In Study 3 ( N  = 360), passersby were less helpful when walking down a street lined with highly exclusive stores, as compared to streets with ordinary stores or no stores. Results, limitations, and directions for future research are discussed.